Prolonged thrombocytopenia and severe transfusion reaction after ABO-incompatible allogeneic hematopoietic stem cell transplantation in a patient with chronic myelomonocytic leukemia - Silva Bermudez, Lina Susana; Heidenreich, Daniela; Klein, Stefan; Wuchter, Patrick; Klüter, Harald; Kayser, Sabine (Transfusion medicine and hemotherapy, 2024)
Introduction: Major ABO-incompatible allogeneic hematopoietic stem cell transplantation (allo-HCT) is a common practice and represents a challenging transfusion scenario. Prolonged thrombocytopenia with increased platelet transfusion needs is one of its reported adverse effects, and this has been linked to the persistence of recipient anti-donor isoagglutinins. Case Presentation: A 55-year-old male patient, O Rh(D)-positive, with chronic myelomonocytic leukemia underwent major incompatible allo-HCT from a A Rh(D)-negative donor. He presented with prolonged thrombocytopenia and multiple transfusion reactions after A Rh(D)-negative platelet transfusions. Considering the outcomes of numerous examinations, we tested the anti-A1 titers, finding a significant persistence of anti-donor isoagglutinins. We limited platelet transfusions to blood group O Rh(D)-negative donors, which significantly decreased the requirement for platelet transfusions. In addition, the transfusion reactions ceased. Conclusion: In case of transfusion reactions against platelet products in major ABO-incompatible allo-HCT patients, isoagglutinin monitoring should be considered and a change in the platelet transfusion protocol may be beneficial in patients presenting high isotiters against recipient’s blood type.